First John structure resolved: Exegetical analysis, Part 2 - Bigalke, Ron J. (HTS teologiese studies, 2013)
Numerous attempts have been suggested regarding the structure of First John. The only nearly unanimous agreement amongst commentators is concerning the prologue (1:1–4) and the conclusion (5:13–21). The lack of unanimity can be frustrating for the majority of those who seek to understand the macrostructure of the First Epistle of John. Consequentially, some commentators have opined that it is impossible to determine a notable structure of First John, and the epistle is thus regarded as a relatively imprecise series of various thoughts that were composed on the basis of mere association. Many exegetes have therefore proposed suggested outlines to aid the understanding of First John as opposed to providing genuine efforts to articulate a discernable structure of the epistle. The final part of this exegetical analysis seeks to demonstrate that exegetes need not succumb to such pessimism because there does appear to be a discernable structure to First John. Providing and stating resolve concerning the First John structure is fundamental for understanding the revealed contents of the epistle.